NON-HAMILTONIAN QUANTUM MECHANICS AND THE NUMERICAL RESEARCHES OF THE ATTRACTOR OF A DYNAMICAL SYSTEM - Weissblut, A.J. (Journal of Information Technologies in Education (ITE), 2012)
This article – introduction to the structural theory of general view dynamical systems, based on construction of dynamic quantum models (DQM), offered by the author. This model is simply connected with traditional model of quantum mechanics (i.e. with the Schrodinger equation). At the same time obtained thus non – Hamiltonian quantum dynamics is easier than classical one: it allow building the clear structural theory and effective algorithms of research for concrete systems. This article is devoted mainly to such task. The algorithm of search for DQM attractors, based on this approach, is offered here.